Electrometallurgy: electrochemical, economic and environmental (3E) aspects - Perica Paunović (Society of Chemists and Technologists of Macedonia, 2011)
This paper is concerned with electrolysis processes aimed for production and refining of metals. This engineering field is named electrometallurgy. The main aspects of electrometallurgy such as electrochemical, energetic/economic and environmental ones are given. The peculiarity of electrorefining and electrowining in both aqueous electrolytes and molten salts are shown. The impact of energetic parameters, such as cell voltage and current efficiency on the economic justification of the electrolysis process is analyzed. It is emphasized that electrolysis is considerably cleaner technology than the pyrometallurgical production and refining of metals.